?Abaham?ana B?a?ml?a - N?uraula Isal?ama, Must?aph?a( 1927-) (?Dh?ak?a: Moh?ammada ?Aminula Haka, 1993)
On the cultural heritage of Bangladesh from ancient times to modern period; collection of contributed articles previously published in the Sundaram, a quarterly journal from Dhaka, Bangladesh.
In Bengali.
Includes bibliographical references.
Keywords: Bangladesh -- -- Civilization